Pengembangan Aplikasi E-Learning Matematika Berbahasa Inggris untuk SMA di Wilayah III Cirebon di Abad 21: Development of English Mathematics E-Learning Applications for Senior High Schools in Region III Cirebon in the 21st Century - Misri, Muhamad Ali; Arrasyid, Farouk Imam; Sofhya, Herlinda Nur’afwa (EDUPEDIA PUBLISHER, 2024)
Purpose: The research aims to develop a learning management system (LMS) for multi-platform use as a mathematics learning medium. Methodology: The methodology employed follows a development model consisting of definition, design, and development stages. During the design phase, an analysis of teachers' and students' needs in mathematics learning using LMS, particularly focusing on materials and functions, is conducted. Additionally, a needs analysis for LMS is performed at this stage. Subsequently, during the design phase, the LMS characteristics and features of the selected system are outlined. In the development stage, feasibility tests and field trials are conducted, incorporating feedback from experts, including program experts (programmers), language experts, and teacher practitioners. Findings: The findings indicate a feasibility level of 93.44%, as assessed by media, material, and language experts. Significance: This suggests its high suitability and effectiveness for implementation.